Interactions between rod-like biopolymer solutions and saliva - Li, Xinxin (2021)
This thesis aims to evaluate underpinning mechanisms of oral processing of polysaccharide thickeners with a rod-like conformation. Xanthan gum (XG) and scleroglucan (SG) are identified as key research targets, with the view to identify the differences and similarities between XG and SG and to assess the potential of SG utilisation as XG analogue in specialised nutrition applications, such as in oropharyngeal dysphagia. Specifically, hydrodynamic properties of SG have been investigated, including hydrodynamic and thermodynamic non-ideality, as well as molecular weight distribution. Furthermore, rheological and lubrication properties have been studied to elucidate complex rheological behaviour of both polysaccharides, as well as to probe their interactions with human whole saliva and bovine submaxillary mucin, used as a saliva-mimicking model. The rheological behaviour was probed using a combination of the steady shear flow, small amplitude oscillatory shear, first normal stress difference and capillary break-up rheometry techniques, whilst lubrication and friction behaviour was examined using the soft-contact tribology method.